2016
DOI: 10.1016/j.colsurfb.2016.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine: Interaction of biomimetic apatite colloidal nanoparticles with human blood components

Abstract: This contribution investigates the interaction of two types of biomimetic-apatite colloidal nanoparticles (negatively-charged 47nm, and positively-charged 190nm NPs) with blood components, namely red blood cells (RBC) and plasma proteins, with the view to inspect their hemocompatibility. The NPs, preliminarily characterized by XRD, FTIR and DLS, showed low hemolysis ratio (typically lower than 5%) illustrating the high compatibility of such NPs with respect to RBC, even at high concentration (up to 10mg/ml). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…Although slightly larger than for incubation in physiological NaCl solution, these results indicate that the apatite NP studied here are biocompatible with regard to RBC and suitable for applications in blood transfusion. These findings agree well with recent studies where the good hemocompatibility of apatite NP was reported, especially concerning direct contact with RBC [31,33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although slightly larger than for incubation in physiological NaCl solution, these results indicate that the apatite NP studied here are biocompatible with regard to RBC and suitable for applications in blood transfusion. These findings agree well with recent studies where the good hemocompatibility of apatite NP was reported, especially concerning direct contact with RBC [31,33].…”
Section: Discussionsupporting
confidence: 93%
“…1b). Based on this hypothesis, and taking into account good hemocompatibility of colloidal apatite NP [33], the aim of the present work was to investigate, for the first time, the possibility of using AEP/HMP stabilized colloidal apatite nanoparticles for facil itating the delivery of trehalose into RBC, in view of promoting their cryopreservation without the use of glycerol. This paper reports experimental data on the role of colloidal apatite NP on RBC viability after freeze thawing cycle and explores, at the molecular scale and by using synthetic lipid bilayers, the mechanism of in teractions between RBC and apatite NP.…”
Section: Introductionmentioning
confidence: 99%
“…There is no aggregation monitored in WBCs, RBCs, and platelets suggesting the level of interaction between plasma proteins and our BS extract are proven aspect to consider for inspecting haemocompatibility. Our data BS intended for use in contact with blood and interaction with plasma proteins which is supporting with bioavailability of NPs alteration and phagocytosis mechanism [48,49].…”
Section: Blood Aggregation Studysupporting
confidence: 71%
“…Nanomaterial interaction with these cells has different effects depending on their intrinsic characteristics. Venkatesan et al [20] and Choimet et al [21] recently reported the high hemocompatibility of chitosan nanoparticles loaded with siRNA-Npr3 and nanoparticles formed with colloidal apatite; however, chitosan nanoparticles dissolved with tripolyphosphate (TPP) to acid pH produce hemolysis [22]. Kim et al [23] carried out rheological measurements and showed that, at concentrations of 12.5 μg/mL, silica nanomaterials caused hemolysis, deformation, and aggregation of erythrocytes.…”
Section: Interaction Of Nanomaterials With Red Cellsmentioning
confidence: 99%